Advertisements
Advertisements
Question
Find the derivative of `2/(x + 1) - x^2/(3x -1)`.
Solution
Let f(x) = `2/(x + 1) - x^2/(3x - 1)`
`f'(x) = d/dx (2/(x + 1)) - d/dx(x^2/(3x - 1))`
= `(|d/dx(2)|(x + 1) - 2d/dx (x + 1))/(x + 1)^2 - (|d/dx(x^2)|(3x - 1) - x^2d/dx (3x - 1))/(3x - 1)^2`
= `(0 - 2 xx 1)/(x + 1)^2 - (2x(3x - 1) - x^2 xx 3)/(3x - 1)^2`
= `(-2)/(x + 1)^2 - (6x^2 - 2x - 3x^2)/(3x - 1)^2`
= `(-2)/(x + 1)^2 - (3x^2 - 2x)/(3x - 1)^2`
= `(-2)/(x + 1)^2 - (x(3x - 2))/(3x - 1)^2`
APPEARS IN
RELATED QUESTIONS
Find the derivative of x–4 (3 – 4x–5).
Find the derivative of the following function (it is to be understood that a, b, c, d, p, q, r and s are fixed non-zero constants and m and n are integers):
`(px+ q) (r/s + s)`
Find the derivative of the following function (it is to be understood that a, b, c, d, p, q, r and s are fixed non-zero constants and m and n are integers):
`a/x^4 = b/x^2 + cos x`
Find the derivative of the following function (it is to be understood that a, b, c, d, p, q, r and s are fixed non-zero constants and m and n are integers):
(ax + b)n (cx + d)m
Find the derivative of the following function (it is to be understood that a, b, c, d, p, q, r and s are fixed non-zero constants and m and n are integers):
`(sin x + cos x)/(sin x - cos x)`
Find the derivative of f (x) = 99x at x = 100
Find the derivative of f (x) = cos x at x = 0
Find the derivative of the following function at the indicated point:
sin x at x =\[\frac{\pi}{2}\]
\[\frac{x + 2}{3x + 5}\]
(x2 + 1) (x − 5)
\[\sqrt{2 x^2 + 1}\]
Differentiate each of the following from first principle:
\[\frac{\cos x}{x}\]
Differentiate each of the following from first principle:
x2 sin x
Differentiate each of the following from first principle:
\[\sqrt{\sin (3x + 1)}\]
Differentiate each of the following from first principle:
\[a^\sqrt{x}\]
tan 2x
(2x2 + 1) (3x + 2)
2 sec x + 3 cot x − 4 tan x
\[\frac{1}{\sin x} + 2^{x + 3} + \frac{4}{\log_x 3}\]
\[\text{ If } y = \left( \sin\frac{x}{2} + \cos\frac{x}{2} \right)^2 , \text{ find } \frac{dy}{dx} at x = \frac{\pi}{6} .\]
\[\text{ If } y = \left( \frac{2 - 3 \cos x}{\sin x} \right), \text{ find } \frac{dy}{dx} at x = \frac{\pi}{4}\]
\[If y = \sqrt{\frac{x}{a}} + \sqrt{\frac{a}{x}}, \text{ prove that } 2xy\frac{dy}{dx} = \left( \frac{x}{a} - \frac{a}{x} \right)\]
x3 sin x
(1 − 2 tan x) (5 + 4 sin x)
(1 +x2) cos x
\[e^x \log \sqrt{x} \tan x\]
x4 (5 sin x − 3 cos x)
\[\frac{e^x}{1 + x^2}\]
\[\frac{x^2 - x + 1}{x^2 + x + 1}\]
\[\frac{x}{1 + \tan x}\]
If \[\frac{\pi}{2}\] then find \[\frac{d}{dx}\left( \sqrt{\frac{1 + \cos 2x}{2}} \right)\]
Write the value of \[\frac{d}{dx}\left( \log \left| x \right| \right)\]
Mark the correct alternative in of the following:
If \[y = \frac{1 + \frac{1}{x^2}}{1 - \frac{1}{x^2}}\] then \[\frac{dy}{dx} =\]
Mark the correct alternative in of the following:
If \[f\left( x \right) = x^{100} + x^{99} + . . . + x + 1\] then \[f'\left( 1 \right)\] is equal to
Find the derivative of 2x4 + x.